Synchronous multimode ultrasound for assessing right-to-left shunt: a prospective clinical study - Yao, Qingyang; Xiong, Huahua; Zhang, Daxue; Ren, Shuqun; Qi, Wenwei; Zou, Xia; Zhao, Yingying; Huang, Shanshan; Wang, Jing; Cao, Liming (Frontiers in Neurology, 2023)
Background Right-to-left shunt (RLS) is associated with several conditions and causes morbidity. In this study, we aimed to evaluate the effectiveness of synchronous multimode ultrasonography in detecting RLS. Methods We prospectively enrolled 423 patients with high clinical suspicion of RLS and divided them into the contrast transcranial Doppler (cTCD) group and synchronous multimode ultrasound group, in which both cTCD and contrast transthoracic echocardiography (cTTE) were performed during the same process of contrast-enhanced ultrasound imaging. The simultaneous test results were compared with those of cTCD alone. Results The positive rates of grade II (22.0%:10.0%) and III (12.7%:10.8%) shunts and the total positive rate (82.1748%) in the synchronous multimode ultrasound group were higher than those in the cTCD alone group. Among patients with RLS grade I in the synchronous multimode ultrasound group, 23 had RLS grade I in cTCD but grade 0 in synchronous cTTE, whereas four had grade I in cTCD but grade 0 in synchronous cTTE. Among patients with RLS grade II in the synchronous multimode ultrasound group, 28 had RLS grade I in cTCD but grade II in synchronous cTTE. Among patients with RLS grade III in the synchronous multimode ultrasound group, four had RLS grade I in cTCD but grade III in synchronous cTTE. Synchronous multimode ultrasound had a sensitivity of 87.5% and specificity of 60.6% in the patent foramen ovale (PFO) diagnosis. Binary logistic regression analyses showed that age (odds ratio [OR] = 1.041) and risk of paradoxical embolism score ≥ 7 (OR = 7.798) were risk factors for stroke recurrence, whereas antiplatelets (OR = 0.590) and PFO closure with antiplatelets (OR = 0.109) were protective factors. Conclusion Synchronous multimodal ultrasound significantly improves the detection rate and test efficiency, quantifies RLS more accurately, and reduces testing risks and medical costs. We conclude that synchronous multimodal ultrasound has significant potential for clinical applications.